Diagnóstico microbiológico: su importancia en el tratamiento y pronóstico periodontal - Botero, Javier Enrique; Arce, Roger; Jaramillo, Adriana; Contreras, Adolfo (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Periodontal disease is characterized by the imbalance between the host-bacteria response resulting in an inflammatory process that initiates the destruction of the periodontal tissues of the tooth. At present it is accepted that the proliferation of microorganism in the subgingival environment is associated with etiopathogenesis of destructive periodontitis. The identification of periodontal pathogens is a rational approach to the diagnosis, treatment and prognosis of periodontal diseases. Several identification techniques have been developed since the beginning of the past century including microscopic evaluation of the dental plaque and modern molecular techniques for the detection of bacterial DNA. Each one of these methods has its advantages and disadvantages. In general, microbiological detection techniques offer useful information on the composition of the subgingival microbiota and, in some cases; it is possible to determine susceptibility to antibiotics (microbial culture). This article reviews and discusses different techniques available for microbial identification and its relevance in the diagnosis, treatment and prognosis of periodontal disease.